Micro-Surgical Treatment of Fetal Myelomeningocele - Mufarrej, Gabriel; Castillo, Gonzalo; Brandão, Maria Anna; Penteado, João Ricardo; Braga, Jair; Filho, Paulo Niemeyer (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2023)
Introduction Myelomeningocele (MMC) is the most common malformation of the central nervous system compatible with life. We will report the results obtained with the prenatal closure of MMC at the Instituto Estadual do Cérebro Paulo Niemeyer (IECPN).Objectives Clinical outcome of fetuses undergoing intrauterine MMC repair by the Peralta mini-hysterotomy. Monitor the reduction of Arnold-Chiari II secondary to MMC, reduction of hydrocephalus and also motor development in these children.Methods Descriptive study of 26 cases with intrauterine MMC repair by mini-hysterotomy, or Peralta technique, performed at the IECPN from December 2017 to February 2020.Results Between December 2017 and February 2020, 26 pregnant women with children with MMC were operated on using Peralta technique. Fetuses were born at an average gestational age of 34.2 weeks and 8% were born before 30 weeks of gestation. The average birth weight was 2096g. It was possible to observe a significant reduction in the occurrence of Arnold-Chiari II in these patients, as well as an evident improvement in motor function in the neurological examination of these babies at the end of the first month of life, where 20 of 23 babies had active movement in the lower limbs.Discussion This study demonstrates the correction of fetal MMC through a mini-hysterotomy of 2.5 to 3.5 cm, developed in order to reduce maternal and fetal mortality. This mini-hysterotomy technique is not a minimally invasive procedure, as it is based on open surgery for the treatment of fetal MMC, as recommended by the Management of Myelomeningocele Study (MOMS).
Keywords: myelomeningocele; fetal surgery; spina bifida; Arnold Chiari II; hydrocephalus